Effect of microstructural anisotropy on the dynamic mechanical behaviour of rolled Ti-6Al-4V - Lock, A.; Brown, A.; Blessington, R.; Appleby-Thomas, G.; Quadir, Md Zakaria; Hazell, P.; Escobedo, J. (2016)
© 2016 by The Minerals, Metals & Materials Society. The effect of microstructural anisotropy on the mechanical behavior of a hot rolled Ti-6Al-4V alloy has been investigated. Quasi-static and dynamic experiments in compression and tension were conducted on specimens with their deformation axis aligned along the rolling (RD), transverse (TD), and through thickness (TT) directions. Digital image correlation (DIC) was utilized to observe in-situ the development of deformation fields. Optic al and electron backscatter diffraction (EBSD) microscopy were conducted on pristine and deformed specimens to examine the microstructural evolution for each loading profile. Initial characterization results show that the plate possesses a preferred orientation of the c-axis along the TD direction and about 40° from the TT. This resulted in the TD direction showing a tensile strength ~12% greater than RD and TT for all loading profiles. Post mortem characterization confirms these results as they reveal the presence of adiabatic shear bands with an accompanying localized re-orientation of the c-axes by ~90°, indicative of substantial tensile twinning.